Skeletal age assessment by measuring planar projections of carpals and distal epiphyses of ulna and radius bones in a sample of South African subadults. Issue 1 (2nd January 2022) - Angelakopoulos, N.; Galić, I.; De Luca, S.; Campobasso, C.P.; Martino, F.; De Micco, F.; Coccia, E.; Cameriere, R.
ABSTRACT: The ratio of the projection of the carpal bones (Bo), and the total area of the carpal bones to the distal ulna and radius epiphyses (Ca), or (Bo/Ca), is a quantitative method for assessing skeletal age in immature subjects. The Cameriere method, based on this ratio, was applied in two samples of 563 South African Black and White subadults (243 boys and 320 girls), aged between 7 and 16 years. The Intraclass Correlation Coefficient (ICC), the Technical Error of Measurement (TEM) (absolute and relative values) and the Coefficient of Reliability (R) for both intra- and inter-examiner agreement were determined and compared. The accuracy was tested by assessing the Standard Error of Estimate (SEE). The results of SEE indicated a method error of 1.19 years and 1.09 years in boys and girls, respectively, and ranged from 0.84 years in 12 year old girls to 3.09 years in 16 year old boys. A one-way analysis of variance showed no statistically significant difference in SA-CA between Blacks and Whites. This method is useful for this population but the results of SEE must be taken into account in forensic contexts and whenever this technique is applied.